MENGATASI KECANDUAN MENONTON FILM PORNO MELALUI LAYANAN KONSELING BEHAVIORISTIK DENGAN TEKNIK OPERANT CONDITIONING PADA REMAJA DESA GROGOLAN PATI - Naharul Muthmainnah; Agung Slamet Kusmanto; Arista Kiswantoro (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
Pornography addiction is a condition in which a person is unable to control their urges and consumption of pornographic content. Constantly watching porn can change a person's mindset and behavior, affect mental health, and interfere with daily life. The objectives of this study are: (1) to find out the factors that cause addiction to watching pornographic films on teenagers in Grogolan Village (2) to overcome addiction to watching pornographic films on teenagers in Grogolan Village through the application of behavioristic counseling operant conditioning techniques. By providing understanding, researchers try to apply behavioristic counseling services with operant conditioning techniques . This research uses qualitative research with a case study type of research. This research was conducted in Grogolan Pati Village with the research subjects being three adolescents (FF, DRP, and AF). The steps to be taken in this case study research are case data collection, case identification, diagnosis, prognosis, treatment and follow up. The data collection techniques used are observation, interview, documentation and home visit techniques. Based on the results of the study, it is concluded that after being given behavioristic counseling with operant conditioning techniques, the counselee is able to change his behavior which makes him addicted to watching pornographic shows, namely the counselee does not search for and watch pono shows, does not buy and store pornographic shows, and the counselee no longer spreads the pono shows he has to his friends. Based on these results, it can be concluded that behavioristic counseling services with operant conditioning techniques can overcome the addiction to watching porn